Genetic Data from Three Accipiter Species, North America, 1996-2014 - Talbot, Sandra L; Pierson, Barbara J; Sonsthagen, Sarah A; Haughey, Christy L (U.S. Geological Survey, 2020)
This data set provides sample collection information and genetic data used to identify relationships between groups of North American accipiters, including one hybrid. Genetic data includes gender identification, nuclear and mtDNA sequence markers, and microsatellite genotypes derived from 20 autosomal loci (Age1302, Age1303, Age1304, Age1305, Age1306, Age1307, Age1308, Age1309, Age1310, Age1311, Age1312, Age1313, Age1314, Age1316, Age1317, Age1318, Age1319, Age1320, Age1321, and Age1322).